Premarital Counseling to Enhance Marriage Preparation in Early Adulthood - Nila Frischa Panzola; Mudjiran; Yeni Karneli (Journal Of Psychology, Counseling And Education, 2024)
Premarital guidance and counseling is an intervention designed to help emerging adults better prepare for marriage. The purpose of this study was to investigate how well premarital guidance and counseling programs work in helping people gain the information and skills necessary to create lasting and healthy marriages. This research methodology consisted of a literature review and analysis of data from numerous premarital counseling studies. The research results show that premarital guidance and counseling can increase individuals' understanding of various aspects of marriage, including effective communication, conflict management, and financial planning. In addition, this program also helps individuals recognize and manage marital expectations and build a strong emotional foundation. Thus, premarital guidance and counseling is highly recommended as a preventive measure to minimize the risk of divorce and improve the quality of married life in early adulthood.